Finite element analysis of tensile notched strength of composite laminates. (1st January 2021) - Divse, Vishwas; Marla, Deepak; Joshi, Suhas S.
Abstract: Stress concentration due to holes (notches) on FRP laminates, a widely used structural material in aerospace applications, often substantially reduces their strength and durability. Some analytical and experimental studies in literature evaluated strength of FRP laminates in the presence of a notch. This work considers stress concentrations factor (SCF), damage progression and tensile notched strength for both GFRP lamina and laminates using finite element (FE) models based on progressive damage analysis. In this work, D / W ratio for holes on 0 ° GFRP lamina varied from 0.1–0.5, by changing hole size from 2.5–12.5 mm. Further, GFRP lamina with four different fibre orientations, and GFRP laminates with three different layups were considered. FE results show that the stress concentration factor (SCF) increases from 3.91 to 5.32 and the tensile notched strength reduces from 435 MPa to 192 MPa, as D / W ratio varies from 0.1–0.5 for 0 ° GFRP lamina. It is found that laminates can be designed with SCF ( < 3 ) that is lower than even an infinite isotropic plate. Further, the axial stiffness of multi-directional laminates degrades during loading due to early damage initiation observed in off-axis plies. Consequently, they show lower axial stiffness and tensile notched strength as compared to unidirectional 0 ° lamina.